The 'cosmopolite' in strange places: provincial cosmopolitanism and a sense of the past in the writings of George Eliot, Henry James, and William Archer's Henrik Ibsen - Wood, SH (2022)
‘Cosmopolitan’ is a disputed term, one of praise and occasionally of abuse. The etymology (kosmopolitês; Greek, ‘citizen of the world’) carries an inbuilt tension between world (kosmos) and citizen or inhabitant of a city (politês). I argue in my thesis that this tension, as played out in the texts I have chosen to study, is not merely between the world and the citizen, but more specifically between the accident of circumstances and the personal instinct to conform and survive. To be a cosmopolite, then, can be an accident that is part of the inscrutable cosmos; yet it can also be a choice enacted by the urbane inhabitant of the polis.